THE EFFECT OF BRAND AWARENESS, SOCIAL MEDIA MARKETING AND BRAND ASSOCIATION ON THE PURCHASE DECISION OF LOCAL SHOES PRODUCTS COMPASS - Suwardi Suwardi (Asosiasi Dosen Muda Indonesia, 2023)
Shoes are the most frequently purchased item by the public, this is because shoes are now not only a necessity for everyone who functions as footwear, but more than that, by following the flow of development, shoes now have a new function, namely for daily needs. lifestyle, one of the local brands that many people choose is Compass. This study aims to determine the effect of brand awareness, social media marketing, and brand association variables on purchasing decisions for local Compass shoe products. The sample was chosen by the people of Bekasi who have never made a decision to buy local shoes from Compass. The data used is primary data, data collection is done by distributing questionnaires to 100 respondents. The test tools used are validity test, reliability test, classic assumption test, multiple linear regression analysis, t test, f test, and the coefficient of determination and the data is processed using SPSS v25 software. The results of this study indicate that brand awareness partially has a significant effect on purchasing decisions, social media marketing variables partially have a significant effect on purchasing decisions, brand association variables partially have a significant effect on purchasing decisions while brand awareness, social media marketing and brand association partially Simultaneously influence the decision to purchase local Compass shoe products.